2020
DOI: 10.3390/ijms21051769
|View full text |Cite
|
Sign up to set email alerts
|

EPA is More Effective than DHA to Improve Depression-Like Behavior, Glia Cell Dysfunction and Hippcampal Apoptosis Signaling in a Chronic Stress-Induced Rat Model of Depression

Abstract: Clinical evidence indicated that eicosapentaenoic acid (EPA) was more effective than docosahexaenoic acid (DHA) in depression treatment. However, possible mechanisms remain unclear. Here, a chronic unpredictable mild stress (CUMS)-induced model of depression was used to compare EPA and DHA anti-depressant effects. After EPA or DHA feeding, depression-like behavior, brain n-3/n-6 PUFAs profile, serum corticosterone and cholesterol concentration, hippocampal neurotransmitters, microglial and astrocyte related fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 52 publications
(70 reference statements)
11
61
0
Order By: Relevance
“…tended to have lower serum total cholesterol content p 0.09 than the DHA group. These findings were supported by a previous study where the EPA diet was found to be more effective at lowering serum total cholesterol content than the DHA diet 29 . In a human study, the increased HDLcholesterol level caused by DHA intake compared to EPA intake has been suggested to involve the inhibition of cholesteryl ester transfer protein CETP activity by DHA 30 .…”
Section: Discussionsupporting
confidence: 82%
“…tended to have lower serum total cholesterol content p 0.09 than the DHA group. These findings were supported by a previous study where the EPA diet was found to be more effective at lowering serum total cholesterol content than the DHA diet 29 . In a human study, the increased HDLcholesterol level caused by DHA intake compared to EPA intake has been suggested to involve the inhibition of cholesteryl ester transfer protein CETP activity by DHA 30 .…”
Section: Discussionsupporting
confidence: 82%
“…The CUMS paradigm on mice was adapted from past research. In total, 11 different stressors were presented randomly twice a day for a total of 49 consecutive days [35][36][37].…”
Section: Cums Modelmentioning
confidence: 99%
“…A CMS study demonstrated that EPA and DHA can improve aberrant corticos-terone and IL-1β levels as well as hippocampal noradrenaline and 5-hydroxytryptamine concentrations. The researchers also reported that n-3 PUFAs can ameliorate microglial and astrocyte functions suppressed by CMS stimuli and improve depressive symptoms of rodent animals 88) . Notably, studies on models of brain development have indicated that n-3 PUFA supplementation reduces microglial activation or cause phenotype alteration.…”
Section: Possible Cellular Mechanisms Underlying the Antiinflammatory Effects Of N-3 Pufamentioning
confidence: 96%